Urban Morphology and Outdoor Microclimate around the “Shophouse” Dwellings in Ho Chi Minh City, Vietnam - Hung Thanh Dang; Adrian Pitts (Buildings, 2020)
The underestimation of population growth has resulted in the disruptive and uncontrolled expansion of settlements in Ho Chi Minh City (HCMC). The outcome is a complicated mix of new spontaneous dwelling areas featuring a number of distinct urban morphologies. Previous studies have shown the impacts of urban morphologies on comfort levels in outdoor environments. The paper examines the correlation of microclimatic conditions and constituents that create the urban spatial form of residential neighbourhoods, particularly around ‘shophouse’ buildings. Understanding that relationship is significant for improving the future planning and design of residential zones and the creation of a pleasant external environment. Seven urban dwelling patterns were studied. Thermal variables were measured on-site over a summer season, while meteorological data were recorded. Additionally, numerical studies of the microclimate around two sample sites showed variations owing to different urban contexts. During summer, the outdoor conditions for the types surveyed ranged from 29.5 to 38.0 °C air temperature, 41% to 79% humidity, and 0.1 to 0.9 m/s airspeed at the occupied level. Environmental variations averaged 1.5 °C, 7% relative humidity, and 0.3 m/s between the urban geometries. Occupant thermal satisfaction was found around formally planned dwelling blocks, while compact neighbourhoods were characterised by cooler temperatures, but poor airflow and daylight. The outcomes are significant for optimising urban and building design.